The Business Analyst as Strategist - Hass, Kathleen (Berrett-Koehler Publishers, 2007)
An organization's ability to achieve strategic goals through programs and supporting projects depends on its ability to establish a future vision, set strategic goals, select the most valuable projects, and then execute flawlessly. Organizational strategic alignment is achieved by converting strategic plans and goals into a valuable portfolio of programs and supporting projects. Strategic project leaders and project teams execute the project plans to meet objectives and deliver project outcomes, adding value to the organization. As the role of the business analyst evolves and matures, senior business analysts will emerge as the key individuals in the organization who have the depth of business acumen and technological proficiency to serve as both business and technology experts. In this capacity, business analysts will become involved in an array of activities designed to devise a strategy to reach the organization's future business vision by achieving strategic goals. As the business analyst elevates into a leadership role as the business and technology strategist, he or she serves the executive team by facilitating, informing, and enabling the most favorable business decisions during the strategic planning and enterprise analysis phases of the business solution life cycle (BSLC). This book examines the emerging critical role of the business analyst during these first two phases of the BSLC.